Analyzing electrocardiographic, echocardiographic, and cardiac marker changes in organophosphorus poisoning cases at a tertiary care hospital of Jharkhand, India - Punam K. Munda; Diljeet Bodra; Parul Singh; Krati Agarwal (Journal of Family Medicine and Primary Care)
Introduction: Organophosphorus insecticides, widely used worldwide, are a significant public health risk in developing countries, causing 3 million poisonings and 300,000 deaths annually. Despite a 20% fatality rate in Asia, improved care is reducing mortality. Improper storage and accessibility contribute to frequent suicides, especially among lower socio-economic groups. Cardiac complications, often fatal, are preventable with early treatment. This study examines 60 acute poisoning cases at RIMS, Ranchi, highlighting the need for improved management. Material and Methods: This prospective clinical study, conducted from May 2018 to November 2019, involved 60 patients with acute organophosphorus poisoning admitted within 24 hours of ingestion. Comprehensive management included gastric lavage, activated charcoal, antidotes (atropine and pralidoxime), and supportive measures. Clinical and biochemical assessments, including echocardiography, monitored patient progress and treatment outcomes. Results: In a study of 60 acute organophosphorus poisoning cases, common early symptoms included lacrimation, salivation, blurring vision, nausea, and vomiting. Pupil constriction was an early sign. Bradycardia occurred in 46.67% of patients. Despite intensive care, 6.67% succumbed, with causes including ventricular fibrillation, aspiration pneumonia, and non-cardiogenic pulmonary edema. Conclusion: Future studies should address the infrastructural gaps of this study, as acute organophosphate poisoning constitutes over 75% of hospital poisoning cases. Early recognition and prompt treatment of cardiac complications can prevent fatalities, highlighting the need for improved management protocols and healthcare infrastructure.